Analysis of Character Education Values in the Film Iqro: The Adventure of Reaching for the Stars by Iqbal Alfajri - Yanti, Susri; Alam, Masnur (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
This study analyzes character education values in the Indonesian film Iqro: Petualangan Meraih Bintang directed by Iqbal Alfajri. The research aims to explain the relevance of character education values, the strategies used by the grandfather character to internalize those values to his granddaughter, and the specific character traits depicted in the film. Employing a qualitative descriptive approach with content analysis, the study applies Roland Barthes’ semiotic theory focusing on denotation and connotation to interpret scenes, dialogues, and symbols. The prim ary data source is the film itself, while secondary data are derived from relevant books, journal articles, and online resources. Findings reveal three main character education values strongly represented in the film: (1) perseverance, as seen in Aqila’s determination to prove astronomical facts and fulfill her grandfather’s requirement to learn the Qur’an before using the observatory telescope; (2) sincerity, reflected in the grandfather’s dedication to nurturing Aqila’s character and defending the Bosscha Observatory from threats of hotel construction; and (3) religious literacy, highlighted through the integration of Qur’anic verses with scientific learning about the universe. The study concludes that the film effectively conveys Islamic character education through relatable narratives, inspiring young audiences to combine knowledge seeking with moral and spiritual growth. These findings imply that films with moral and educational content can be an effective medium for character building in Islamic education contexts.